Nationwide questionnaire data of 229 Williams-Beuren syndrome patients using WhatsApp tool - Lucas Vieira Lacerda Pires; Rogério Lemos Ribeiro; Adriana Modesto de Sousa; Bianca Domit Werner Linnenkamp; Sue Ellen Pontes; Maria Cristina Triguero Veloz Teixeira; Debora Maria Befi-Lopes; Rachel Sayuri Honjo; Debora Romeo Bertola; Chong Ae Kim (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Williams-Beuren syndrome is a multisystemic disorder caused by a microdeletion of the 7q11.23 region. Although familial cases with autosomal dominant inheritance have been reported, the vast majority are sporadic. Objective: To investigate the main complaints and clinical findings of patients with Williams-Beuren syndrome. Methods: A total of 757 parents of patients registered in the Brazilian Association of Williams-Beuren Syndrome (ABSW) received a questionnaire via WhatsApp from March to July 2017. Results: In total, 229 parents answered the survey. Age of diagnosis ranged from 2 days to 34 years (median: 3 years). The main clinical findings reported by the parents were abdominal colic (83.3%), failure to thrive (71.5%), feeding difficulty in the first year (68.9%), otitis (56.6%), urinary tract infections (31.9%), precocious puberty (27.1%) and scoliosis (15.9%). Cardiac defects were present in 66% of patients, and the most frequent defect was supravalvular aortic stenosis (36%). Arterial hypertension was reported in 23%. Hypercalcemia was reported in 10.5% of patients, mainly during the first year of life. Hyperacusis and hypersociability were common complaints (both present in 89%). Other behavioral and neuropsychiatric symptoms reported by the parents included attention deficit (89%), anger crises (83%), excessive fear (66%), depression (64%), anxiety (67%) and hypersexuality (33%). The most common complaints were hypersensitivity to sounds, talkative personality, emotional dependence and learning difficulties. In 98.3%, the parents denied family history. Conclusions: Williams-Beuren syndrome requires close follow-up with different medical specialties due to their variable clinical comorbidities, including language and school learning difficulties, behavioral and psychiatric problems.